Effect of omega-3 polyunsaturated fatty acid (n-3 PUFA) supplementation to lactating sows on growth and indicators of stress in the postweaned pig12. (23rd September 2019) - McAfee, John M; Kattesh, Henry G; Lindemann, Merlin D; Voy, Brynn H; Kojima, Cheryl J; Burdick Sanchez, Nicole C; Carroll, Jeff A; Gillespie, Barbara E; Saxton, Arnold M
Abstract: Dietary omega-3 polyunsaturated fatty acids (n-3 PUFA ) are precursors for lipid metabolites that reduce inflammation. Two experiments were conducted to test the hypothesis that enriching the sow diet in n-3 PUFA during late gestation and throughout lactation reduces stress and inflammation and promotes growth in weaned pigs. A protected fish oil product (PFO; Gromega) was used to enrich the diet in n-3 PUFA. In the initial experiment, time-bred gilts were fed a gestation and lactation diet supplemented with 0% (control; n = 5), 0.25% ( n = 4), 0.5% ( n = 4), or 1% ( n = 5) PFO from 101 ± 2 d of gestation to day 16 of lactation. Adding 1% PFO to the diet increased the n-3:n-6 PUFA ratio in colostrum and milk compared with controls ( P = 0.05). A subsequent experiment was performed to determine whether supplementing the sow diet with 1% PFO improved growth and reduced circulating markers of acute inflammation and stress in the offspring. Plasma was harvested from piglets (16 per treatment group) on day 0 (d of weaning) and days 1 and 3 postweaning. Pigs from the 1% PFO treatment group weighed more ( P = 0.03) on day 3 postweaning and had a greater ( P ˂ 0.05) n-3:n-6 PUFA ratio in plasma on each day sampled compared with 0% PFO controls. There was an overall treatment effect on plasma total cortisol ( P = 0.03) and haptoglobin ( P = 0.04), with lesser concentrations in pigs on the 1% PFO diet. Plasma corticosteroid-binding globulin (CBG ) concentrations were not different between treatment groups but were less ( P ˂ 0.001) on days 1 and 3 when compared with day 0. The resultant free cortisol index [FCI (cortisol/CBG)] was less ( P = 0.02) on days 1 and 3 for pigs from the 1% treatment group compared with the controls. An ex vivo lipopolysaccharide (LPS ) challenge of whole blood collected on days 0 and 1 was used to determine whether 1% PFO attenuated release of inflammatory cytokines (IL-1β, IL-6, and TNF-α). Blood from pigs within the 1% PFO treatment group tended ( P = 0.098) to have a lesser mean concentration of TNF-α in response to LPS compared with blood from controls. These results suggest that providing a PFO supplement as 1% of the diet to sows beginning in late gestation and during lactation can increase the n-3:n-6 PUFA ratio in their offspring, which may improve growth and reduce the acute physiological stress response in the pigs postweaning.